Metodología para la Gestión de Proyectos de Mejora Continua en un Sub-Departamento de Tecnologías de Información en ABC de Costa Rica. - Chaves-Ramírez, Carlos (Instituto Tecnológico de Costa Rica, 2015)
This investigation takes place in the Backup and Recovery sub-team for company ABC. It was originated as to propose a methodology for the management of continuous improvement projects, and thus as a solution to the problem of inefficiency and ineffectiveness of the aforementioned. There is a need to systematize the management of such type of projects, enabling a model that pragmatically enables, executes, and delivers tangible results in less than twelve months. This study parts from a baseline of best practices for project management, then moves to identifying known methodologies for such, and wraps up with workflows, templates and tools that allow for the execution of continuous improvement projects. While determining such baseline, the Backup and Recovery’s sub-department’s current situation and gap analysis was performed, measuring against the CMMI maturity model. In brief, it was determined that the department´s execution urgency derived in projects´ documentation and planning misses. This reinforced negatively on process gaps, lack of objective estimations including risk assessments, failures in scope definition and quality assurance, among others. All the above was later synthesized in an S.W.O.T analysis, singling out the required elements in the proposed solution. The proposed solution contains a simple yet complete methodology, focused in efficiency and effectiveness. It includes a new workflow to initiate, plan, execute, monitor, control and close continuous improvement projects. It also relies on new custom templates and tools, being the minimum required documentation to complete the proposed activities. Key Words: Project Methodology, Projects in Information Technology, Agile, SCRUM, XP
Proyecto de graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos Maestría en Gerencia de Proyectos, 2015.
Keywords: Metodologías; Tecnologías; Servicios de información; Gestión de proyectos